2002
DOI: 10.3171/jns.2002.96.5.0872
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between auditory function and internal auditory canal pressure in patients with vestibular schwannomas

Abstract: Tumor growth into the IAC results in elevation of ICaP and may play a role in hearing loss in patients with VS. The relevance of these findings to the surgical treatment of these tumors is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…17 A recent histopathological study of unresected unilateral acoustic neuromas showed that degenerative changes in the inner ear and atrophy of the stria vascularis and spiral ligament were present in addition to cochlear nerve degeneration when compared with control specimens. 17 Tumor adherence to the cochlear nerve in the IAC 3 as well as increases in IAC pressure from tumor 13 may be responsible for these changes, which have been shown to adversely affect hearing outcome.…”
Section: Hearing Preservationmentioning
confidence: 99%
“…17 A recent histopathological study of unresected unilateral acoustic neuromas showed that degenerative changes in the inner ear and atrophy of the stria vascularis and spiral ligament were present in addition to cochlear nerve degeneration when compared with control specimens. 17 Tumor adherence to the cochlear nerve in the IAC 3 as well as increases in IAC pressure from tumor 13 may be responsible for these changes, which have been shown to adversely affect hearing outcome.…”
Section: Hearing Preservationmentioning
confidence: 99%
“…Perhaps direct damage to primary sensory cells, radiation damage to the cochlear nerve, or direct damage to the nerve or internal auditory artery caused by the lesion result in compression or thrombosis with consequent ischemic damage to the cochlea. 6,27 There are only a few studies in the literature that analyze hearing preservation exclusively in patients with normal or subnormal hearing (GR Class I). Studies regarding the possibility of retaining functional hearing are increasing in number.…”
Section: Hearing Function After Gksmentioning
confidence: 99%
“…In general, there are 4 patterns of hearing loss: 21,27,37,38,51,57,71,72,81,99 1) hearing deterioration in "growing" tumors, 2) hearing deterioration in "nongrowing" tumors, 3) early hearing loss, and 4) sudden hearing loss regardless of tumor growth. Vestibular schwannomas are histologically benign, slow-growing tumors that originate from the Schwann cells of the inferior vestibular nerve in most cases.…”
Section: Mechanism Of Hearing Loss In Vsmentioning
confidence: 99%
“…81 This compromise of the vascular supply can be a result of an increase in intracanalicular pressure or due to direct compression caused by the laterally invading tumor. 7,51 Compression of labyrinthine vessels has been shown to cause degeneration in the organ of Corti and the spiral ganglion (cochlear dysfunction). 22,37,43,71 Of note, the progression of hearing loss in VS is most often gradual, 39,96 although sudden deterioration is also possible.…”
Section: Hearing Loss In Patients With Growing Tumorsmentioning
confidence: 99%
See 1 more Smart Citation